Hyperoodon ampullatus - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (The Canadian field-naturalist, 1982)
Hyperoodon ampullatus (Forster, 1770). In Kalm, Travels into N. Amer., 1:18. TYPE LOCALITY: U.K., England, Essex, Maldon. DISTRIBUTION: Atlantic Ocean, cold temperate to subarctic waters; perhaps also N. Pacific (Hershkovitz, 1966:146). Possibly Mediterranean Sea (OLR). PROTECTED STATUS: CITES - Appendix II as Order Cetacea. ISIS NUMBER: 5301411005002001001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Cetacea, pp. 290-304 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 300, DOI: 10.5281/zenodo.7352983